How the co-inquiry model supports multimodal literacies in early learning settings: a case study of two childcare centres in Western Canada - Fischer, Rhonda (My University, 2025)
In early learning settings, multiple modes of communication are used to help young children convey meaning. These modes, or multimodal literacies, include signs, images, gestures, sounds, speech, movements, and actions. This study adds a deeper understanding of the strategies educators in Alberta use to support multimodal literacies. I conducted a multiple case study with eight educators at two childcare centers. To collect data, I utilized video walk-throughs whereby educators showed me around their playrooms digitally, interviews with early childhood educators, and pedagogical documentation in the form of learning stories collected from educators to further my understanding of how multimodal literacies are supported in early childhood settings. This research revealed that educators use multiple strategies to support multimodal literacies, including an emergent curriculum using the co-inquiry model of observation, reflection, and planning next steps. Implications include the need for early learning and childcare educators to use a broad view of multimodal literacies and a co-inquiry model first to observe the children’s multimodal literacies, then reflect on their observations, and then nurture or extend these literacy practices.
Keywords: early childhood literacy; multimodal literacy; emergent curriculum; co-inquiry model